IMPLEMENTASI ALGORITMA PRIM PADA JARINGAN DISTRIBUSI LISTRIK PRIMER DENGAN MENGGUNAKAN PROGRAM BERBASIS GIS - Nugraha, Deny Wiria (MEKTEK, 2011)
Optimization problem is the demanding problem for optimum solutions. The optimum (best) solution is asolution with minimum values, or maximum among a set of possible alternative solutions. In electricaldistribution network, problem of demanding achievement of optimum condition of system operationalperformance is essential. One of the factors necessary to consider in the designing of the primary electricaldistribution network is cost. Cost is closely related to length of cable used. It highlights the importance ofcalculating the minimum length of cable required in a network. The cable should be not only with as minimalas possible in length, but also regulated for better arrangement.Actually, in regulating the cable installation, longer path is more frequently selected. One of the ways ofachieving optimization condition is to use algorithm to determine a minimum spanning tree of the primaryelectrical distribution network system. In this study, the algorithm used is Prim’s algorithm.The research was conducted by designing a graph model of primary electrical distribution network inappropriate with the data obtained. Based on the graph, each was weighted for distance or length of networkcable by using the ArcView GIS 3.3. The data were then calculated and simulated by using computer to gaina minimum spanning tree of the primary electrical distribution network using the Prim’s algorithm